The implementation of ICT in English subjects to increase student’s motivation in learning at SMAN Negeri 16 Batam - Pebiana Pebiana; Theodesia Lady Pratiwi (Universitas Internasional Batam, 2023)
Technology development is used to improve academic and non-academic students’ abilities in education. Many platforms and devices offer interesting material designs for learning activities. Attractive and sophisticated material design can increase students' motivation and interest in learning. The implementation of ICT in English subjects is done at SMAN Negeri 16 Batam to increase students’ motivation in learning. Interviews and questionnaires are conducted with the English teacher and students in grade XI of the Social Sciences Major. The Likert scale is designed as an instrument that consists of statements for data analysis. Through Google Forms will be shared online, students can fill in the questionnaires. The author conducts the interview face-to-face to obtain information based on the teacher’s point of view. The results will determine and identify issues for implementing ICT in the school. The author will decide on the teaching media and create material that is suitable for students based on the result of the data analysis. The output of this project is Lesson Plan, Teaching materials and assessments design that integrate ICT. The author introduces ICT through Microsite for assisting the teacher in teaching English. Lastly, the author concludes the result through the response of the partner.